2020
DOI: 10.1002/fsn3.1873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking locally available common bean (Obwelu) on iron and zinc retention, and pumpkin (Sweet cream) on provitamin A carotenoid retention in rural Uganda

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…A study by Carvalho et al (2014) indicates that either boiling or steaming pumpkin retains over 100% of PVACs, b-carotene and a-carotene. These findings are consistent with Buzigi, Pillay, and Siwela (2020b) and Azizah et al (2009), who showed that either boiling or steaming pumpkin retained over 100% of b-carotene and a-carotene. Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015).…”
Section: Home Cooking Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…A study by Carvalho et al (2014) indicates that either boiling or steaming pumpkin retains over 100% of PVACs, b-carotene and a-carotene. These findings are consistent with Buzigi, Pillay, and Siwela (2020b) and Azizah et al (2009), who showed that either boiling or steaming pumpkin retained over 100% of b-carotene and a-carotene. Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015).…”
Section: Home Cooking Methodssupporting
confidence: 91%
“…Over 90% of childhood VAD in LMICs is found in SSA and Asia (Stevens et al, 2015). However, based on Table 2, several LMICs from SSA (Buzigi, Pillay, and Siwela 2020b;Pepping, Vencken, and West 1988) and Asia (Koh and Loh 2018;Norshazila et al 2014;Pandey et al 2003;Usha, Lakshmi, and Ranjani 2010), cultivate pumpkin. Therefore, these findings may indicate that there is an existing opportunity to promote and support the utilization of pumpkin as a CF to combat childhood VAD in SSA and Asia.…”
Section: Pumpkin Varieties In Low and Middle Income Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, respondents might have forgotten to mention all the foods they consumed in the previous 7 days, leading to over estimation of poor food consumption status. It is worth noting that Uganda food aid recipients, mainly HHs headed by women were worried about on how they would cook food aid items such as common bean [ 36 ], which have a long cooking time [ 60 ]. Therefore, it is likely that some HHs that received food aid items did not consume it because they lacked fuel for cooking.…”
Section: Discussionmentioning
confidence: 99%
“…The village health team members (community health workers) identified five expert peer mothers from the local community and invited them to Bwera Hospital kitchen to participate in the preparation of the study composite dishes. Expert peer mothers were encouraged to prepare the composite dishes using locally acceptable home-based methods used in the community to prepare common beans and sweet with prior soaking because they argued that soaking softens common beans to reduce cooking time and saves fuel as reported in a previous Ugandan study (Buzigi et al, 2020c). The IBCB and NIBCB were cooked separately using a local stove (Esigiri) until they were soft and ready for human consumption.…”
Section: Preparation Of Test and Control Composite Dishesmentioning
confidence: 99%